Advanced Age Is Associated With Catatonia in Critical Illness: Results From the Delirium and Catatonia Prospective Cohort Investigation - Connell, Jennifer; Kim, Ahra; Brummel, Nathan E.; Patel, Mayur B.; Vandekar, Simon N.; Pandharipande, Pratik; Dittus, Robert S.; Heckers, Stephan; Ely, E. Wes; Wilson, Jo Ellen (Frontiers in Psychiatry, 2021)
Introduction: Catatonia, characterized by motor, behavioral and affective abnormalities, frequently co-occurs with delirium during critical illness. Advanced age is a known risk factor for development of delirium. However, the association between age and catatonia has not been described. We aim to describe the occurrence of catatonia, delirium, and coma by age group in a critically ill, adult population. Design: Convenience cohort, nested within 2 clinical trials and 2 observational cohort studies. Setting: Single academic medical center in Nashville, TN. Patients: 378 critically ill adult patients on mechanical ventilation and/or vasopressors. Measurements and Main Results: Patients were assessed for catatonia, delirium, and coma by independent and blinded personnel, the Bush Francis Catatonia Rating Scale, the Confusion Assessment Method for the ICU and the Richmond Agitation and Sedation Scale. The most common causes of admission were trauma in the youngest age group (47%) and sepsis/septic shock in all other groups (30%, 26%, and 24% by increasing age quartiles). Of 378 patients, 23% met diagnostic criteria for catatonia, 66% experienced delirium, and 52% experienced coma during the period of observation. The prevalence of catatonia, co-occurring catatonia and delirium, and co-occurring catatonia and coma increased significantly with advancing age group (p values <0.05). There was no relationship found between age and catatonia severity or age and presence of specific catatonia items. Conclusion: Given the significant relationship between age and catatonia, these data demonstrate catatonia’s association with advanced age in critical illness. Future studies should explore if cognitive morbidities associated with delirium also occur following catatonia.